Far-Field Earthquake Responses of Overhead Line Equipment (OHLE) Structure Considering Soil-Structure Interaction - Ngamkhanong, Chayut; Kaewunruen, Sakdirat; Baniotopoulos, Charalampos (Frontiers in Built Environment, 2018)
Overhead line equipment (OHLE) is the components for the electric train which supply the electric power to the train. For one or two tracks, OHLE is normally supported by cantilever mast. The cantilever mast, which is made of H-section steel, is slender and has a poor dynamic behavior by nature. Nonetheless, the mast structures, which located alongside the railway track, have not been fully studied on the dynamic behavior. This paper presents the effects of far-field excitations on cantilever mast and overhead contact wire. The five far-field earthquake records at various magnitudes between 6.5 and 8 Mw are considered. A three-dimensional mast structure with varying support stiffness is made using finite element modeling. It is interesting that support stiffness plays a role in the dynamic responses of OHLE during far-field earthquakes due to the change of its properties. Surprisingly, the earthquakes can cause damage to the overhead contact wire which lead to the failure of electric system. In this case, the train cannot run until the broken wire and electric system is cleared. This occurs when there are the losses of support stiffness due to the failure of support connection or soil degradation. Moreover, beating phenomenon, which normally occurs in the tall building, is obviously observed in OHLE during the occurrence of earthquake. This is the world first to demonstrate the effects of far-field earthquakes on the cantilever mast structure and the response of OHLE. The insight in this earthquake response of OHLE and its support has raised the awareness of engineers for better design of cantilever mast structure and its support condition. The outcome of this study will provide a new earthquake detection method using OHLE.